Nematodes from galls on Myrtaceae. IV. Fergusobia from flat leaf galls on Eucalyptus and Corymbia, with descriptions of two new species - Davies, Kerrie A.; Giblin-Davis, Robin M.; Ye, Weimin; Taylor, Gary S.; Thomas, W. Kelley (Zootaxa, 2013)
Two new species of Fergusobia are described. Both were collected from flat leaf galls from South Australia, one on Eucalyptus microcarpa and the other on E. porosa. Fergusobia microcarpae n. sp. Davies is characterised by the combination of a C-shaped parthenogenetic female with a short, broadly rounded conoid tail, an arcuate to open C-shaped infective female with an hemispherical tail tip, and arcuate to J-shaped males with angular spicules and short peloderan bursa. Fergusobia porosae n. sp. Davies is similar in having an arcuate to C-shaped parthenogenetic female with a small conoid tail, an almost straight to arcuate infective female with an hemispherical tail tip, and males that are almost straight to barely J-shaped with angular spicules and short peloderan bursa. They differ in that the bodies of parthenogenetic and infective females of F. microcarpae n. sp. are more curved than in F. porosae n. sp. Other known similar forms of Fergusobia/Fergusonina galls are outlined and the larval shield morphologies of their associated mutualistic Fergusonina fly species are discussed where known. An inventory of all known Fergusobia/Fergusonina associations from flat leaf galls from Corymbia spp. and Eucalyptus spp. is presented. Relationships of Fergusobia nematodes were inferred from analysis of sequences of 28S rDNA D2/D3 domains and a portion of mitochondrial DNA cytochrome oxidase subunit I (mtCOI). Nematodes from flat leaf galls appeared in two clades.